Negative Factors Affecting the Sleep Quality of the Elderly in Iran: A Systematic Review - Saideh Sadat Mortazavi; Elham Nasiri; Mahshid Foroughan; Seyed Ali Hosseini; Fatemeh Shahbazi (University of Social Welfare and Rehabilitation Sciences, 2021)
Objective: As age increases, different physical and mental problems, including sleep disorders, occur in the elderly. The Person-Environment-Occupation (PEO) model is one of the most common practical models in occupational therapy. The current study aims to review negative factors affecting the sleeping quality of the elderly in Iran based on the PEO model. Materials & Methods: According to PRISMA (the preferred reporting items for systematic reviews and meta-analyses) guidelines and in this systematic review study, we searched Google Scholar, Scopus, PubMed, Magiran, IranMedex, and SID databases using the keywords of "Elderly", "aging", "geriatric", "older adult", "Iran", and "sleep" in English and Persian articles published from 2010 to 2019. Studies on the sleep problems of other age groups, letters to the editor, duplicate studies, studies on non-Iranian seniors, studies published in languages other than Persian and English, and those with unavailable full-texts were excluded. In the next stage, the titles and abstracts of the retrieved articles were independently reviewed by two researchers to identify the studies that meet the inclusion criteria. The dispute was resolved through discussion and reaching an agreement. Then, the full text of eligible articles was retrieved. Articles approved based on at least 20 out of 22 items of the STROBE (strengthening the reporting of observational studies in epidemiology) checklist were included in the study. Finally, 24 articles that were in line with the research objectives were selected for an in-depth review. Results: Out of 24 studies, 11 reported quantitative sleep problems, 9 of which claimed that more than 70% of the elderly had sleep problems. The negative factors affecting the sleep quality of Iranian older adults were presented and categorized based on personal, environmental, and occupational factors. Eighteen articles addressed personal factors, where the most common factor was related to personal health issues. Eleven articles reported environmental factors, where the most common factor was related to the physical environment. In three articles, the factors that had a negative effect on sleeping are occupational and included the change of sleeping place and not talking to others before going to bed. Conclusion: Personal factors (e.g. aging, female gender, disease), environmental factors (e.g. lack of communication with relatives and friends, inappropriate physical environment, and living in a nursing home), and occupational factors (e.g. change of sleeping place, hospitalization, and not talking to others before going to sleep) are negative factors affecting the sleep quality of the elderly in Iran.